Monsoonal variations of lead (Pb) in coastal waters around Singapore - Chen, Mengli (2022)
Anthropogenic lead (Pb) has been the overwhelming Pb source to the global ocean, primarily contributed from Pb gasoline and industrial emissions. However, since Pb gasoline has been phased out globally, questions about whether there was a decrease in seawater Pb concentration, or if there are other sources taking over remains unclear in Southeast Asia. Here, combining Pb concentrations in seawater from Singapore Strait in 2010-2017; trap sediment in 2018-2019; and the previously published coral reconstruction covering 1975-2010; we found that the seawater Pb concentration in Singapore Strait over past decades followed the regional gasoline emissions, and no additional major source had contributed the Pb in the seawater since ~2010. The present-day Pb in Singapore Straits' water mainly follows the monsoonal current reversals, with variable degrees of scavenging that peak in inter-monsoon season. Minor Pb sources still contribute to some local-scale variabilities, despite a decadal-scale decreasing trend of Pb in seawater.